Excessive response to provocation rather than disinhibition mediates irritable behaviour in Huntington’s disease - McLauchlan, Duncan James; Linden, David E. J.; Rosser, Anne E. (Frontiers in Neuroscience, 2022)
Background Irritable and impulsive behaviour are common in Huntington’s disease (HD: an autosomal dominant disorder causing degeneration in cortico-striatal networks). However, the cognitive mechanisms underlying these symptoms remain unclear, and previous research has not determined if common mechanisms underpin both symptoms. Here we used established and novel tasks to probe different aspects of irritable and impulsive behaviour to determine the neural mechanisms involved. Methods We recruited a cohort of 53 gene positive HD participants and 26 controls from non-affected family members and local volunteers. We used established questionnaire measures of irritability in HD (Snaith Irritability Scale, Problem Behaviours Assessment) and impulsivity (UPPSP, Barratt Impulsivity Scale), in addition to cognitive tasks of provocation, motor inhibition, delay discounting and decision making under uncertainty. We used generalised linear models to determine differences between cases and controls, and associations with irritability in the HD group. Results We found differences between cases and controls on the negative urgency subscale of the UPPSP, which was associated with irritability in HD. The frustrative non-reward provocation task also showed differences between cases and controls, in addition to predicting irritability in HD. The stop signal reaction time task showed case-control differences but was not associated with irritability in HD. None of the other measures showed group differences or predicted irritability in HD after correcting for confounding variables. Discussion Irritability in HD is mediated by excessive response to provocation, rather than a failure of motor inhibition.